The Sufi path of love : the spiritual teachings of Rumi - Jalāl al-Dīn Rūmī, Maulana, 1207-1273 (SUNY series in Islam., 1983)
This is the most accessible work in English on the greatest mystical poet of Islam, providing a survey of the basic Sufi and Islamic doctrines concerning God and the world, the role of man in the cosmos, the need for religion, man's ultimate becoming, the states and stations of the mystical ascent to God, and the means whereby literature employs symbols to express "unseen" realities. William Chittick translates into English for the first time certain aspects of Rumi's work. He selects and rearranges Rumi's poetry and prose in order to leave aside unnecessary complications characteristic of other English translations and to present Rumi's ideas in an orderly fashion, yet in his own words. Thorough, nontechnical introductions to each chapter, and selections that gradually present a greater variety of terms and images, make this work easily accessible to those interested in the spirituality of any tradition.